PRAKTIK KEPEMIMPINAN ISLAM YANG DIHARAPKAN OLEH KARYAWAN (STUDI KASUS PADA RUMAH SAKIT ISLAM PKU MUHAMMADIYAH PEKAJANGAN) - Farodis, Zahrotul; Mas’ud, Fuad (Diponegoro Journal of Management, 2020)
Leadership is one aspect of the organization that is needed both in generalorganizations and not for profit organizations, because leadership is one of the keys to thesuccess of an organization. Rumah Sakit Islam PKU Muhammadiyah Pekajangan, whichis a social organization owned by an Islamic organization that is Muhammadiyah which isengaged in health services. Carrying the name of Islam, of course leadership applied isIslamic leadership, both in management and service aspects always trying to provide it inaccordance with Islamic values. in 2019, the inauguration of the syar’i hospitalcertification emerged. This is a new challenge for Islamic hospitals, because there was aneed for change management to further deepen Islamic values. In the process of change, ittakes the role of a leader. Leaders who have attributes in accordance with employeeexpectations will be easier to bring the organization in the process of preparing theorganization to face the syar’i hospital certification. This research aim to find Islamicleadership practice that have attributes in accordance with expectations by employees.Implicit Leaderhip Theory were used to to find those attributes.This study was using qualitative methods that started from in depth-interviews andobservation. Firstly the respondents are chosen with several requirements such as have aminimum tenure of five years. Secondly, respondents were interviewed with questions thathad been prepared. Thridly, observations carried out to see the actual situation.The results show that Islamic leadership needs to be adopted by all leaders of RSIPKU Muhammadiyah Pekajangan on practical level. Morever, by implementing alldimensions of core leadership functions with Islamic Leadership guidance, will be fulfilledemployees wish that has becomes their motivation to achieved the Syar’I hospitalcertification.